PERC battery and preparation method thereof

During the preparation process of PERC batteries, the phosphorus silicon glass on the back of the silicon wafer is removed and alkaline-polished and single-sided fleece-making treatment is carried out to form a small suede structure, which solves the problem of poor photoelectric conversion efficiency of existing PERC batteries and achieves higher photoelectric conversion efficiency and current output.

CN119815956APending Publication Date: 2025-04-11DAS SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311293395.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-07
Publication Date
2025-04-11

Smart Images

  • Figure CN119815956A_ABST
    Figure CN119815956A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a PERC cell and a preparation method thereof, and according to the preparation method of the PERC cell provided by the embodiment of the invention, under the condition that front borosilicate glass is used as a mask of a front suede, a micro-texturing process is added to a back surface subjected to alkali polishing treatment, so that a small suede structure is prepared on the back surface of a solar cell; the small suede structure has the advantages that the absorption of long-wave light can be improved, the current of the cell is increased, the back efficiency of the cell is improved, the cell efficiency and the double-sided rate are increased, meanwhile, attachment points are provided for nucleation of back silver paste or aluminum paste in the printing process, the contact capacity of the silver paste and a silicon wafer is improved, and cell filling is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of crystalline silicon solar cell manufacturing, and in particular to a PERC cell and a preparation method thereof. Background Art

[0002] Due to the passivation of the back surface dielectric film and the use of local metal contact, the surface recombination rate is greatly reduced, while the light reflection of the back surface is improved, making the PERC cell have a higher photoelectric conversion efficiency.

[0003] Currently, the manufacturing process of PERC cells includes at least seven steps, including texturing, diffusion, etching, annealing, back film, front film and printing. Among them, the etching process is to polish the back of the cell. The back velvet structure is relatively flat, and the reflectivity of light is 40-50%, resulting in poor photoelectric conversion efficiency of the cell. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a PERC cell and a preparation method thereof, so as to solve the problem of poor photoelectric conversion efficiency of the PERC cell formed by the existing preparation method.

[0005] In order to solve the above problems, the present invention is achieved through the following technical solutions:

[0006] The present invention provides a method for preparing a PERC battery, which comprises:

[0007] After the single crystal silicon wafer is subjected to double-sided texturing and phosphorus diffusion treatment in sequence, the phosphorus silicon glass on the back side of the silicon wafer is removed;

[0008] After removing the phosphorus silicon glass on the back side, the back side of the silicon wafer is subjected to alkali polishing;

[0009] After the alkali polishing treatment, the back side of the silicon wafer is subjected to a single-side texturing treatment;

[0010] After single-sided texturing, removing the phosphosilicate glass on the front side of the silicon wafer;

[0011] After removing the phosphosilicate glass on the front side, a passivation film layer, an anti-reflection layer and an electrode are formed on the surface of the silicon wafer to produce a PERC cell.

[0012] Furthermore, in the method for preparing the PERC cell, the back side of the silicon wafer is subjected to a single-side texturing treatment, comprising:

[0013] The back side of the silicon wafer is wet-textured using a first texturizing liquid, wherein the first texturizing liquid includes, by volume, 12 to 18 parts of 45% concentrated KOH, 1 to 2 parts of a first texturizing additive and 400 to 500 parts of pure water, wherein the first texturizing additive includes isotridecanol ether, acrylamide, quaternary ammonium salt, disodium tetraacetate, alkyl glycoside and sodium benzoate.

[0014] Furthermore, in the preparation method of the PERC battery, in the first texturing additive, the mass percentage of isotridecanol ether is 2-3%, the mass percentage of acrylamide is 0.5-2%, the mass percentage of quaternary ammonium salt is 1-3%, the mass percentage of disodium tetraacetate is 1-3%, the mass percentage of alkyl glycoside is 3-4%, the mass percentage of sodium benzoate is 0.3-0.5%, and the balance is water.

[0015] Furthermore, in the preparation method of the PERC battery, the single-side texturing treatment time is 80 to 150 seconds, and the treatment temperature is 70 to 80°C.

[0016] Furthermore, in the preparation method of the PERC cell, after single-sided texturing treatment, the reflectivity of the back side of the silicon wafer is between 25% and 40%.

[0017] Furthermore, in the preparation method of the PERC cell, the phosphorus diffusion treatment includes:

[0018] Phosphorus diffusion deposition is performed on the silicon wafer for 10 to 15 minutes at a temperature of 770 to 790°C, a pressure of 70 to 120 mbar, a nitrogen flow rate of 500 to 800 sccm / min carrying phosphorus oxychloride, and an oxygen flow rate of 400 to 600 sccm / min. The temperature is then raised to 850 to 900°C, the pressure is 80 to 120 mbar, and the nitrogen flow rate is 2000 to 4000 sccm / min for 10 to 20 minutes.

[0019] Furthermore, in the preparation method of the PERC cell, after the phosphorus diffusion treatment, the thickness of the phosphosilicate glass on the front side of the silicon wafer is greater than or equal to 30 nm.

[0020] Furthermore, in the method for preparing the PERC cell, removing the phosphosilicate glass on the back side of the silicon wafer comprises:

[0021] The back side of the silicon wafer is chain pickled using hydrofluoric acid with a mass percentage of 4.9 to 9.8%;

[0022] Removing the phosphosilicate glass on the front side of the silicon wafer, comprising:

[0023] The front side of the silicon wafer is chain pickled using hydrofluoric acid with a mass percentage of 4.9-9.8%.

[0024] Furthermore, in the method for preparing the PERC cell, the double-sided texturing comprises:

[0025] The back side of the silicon wafer is wet-textured using a second texturizing liquid, wherein the second texturizing liquid includes, by volume, 2 to 6 parts of 45% concentrated KOH, 1 to 2 parts of a second texturizing additive and 80 to 100 parts of pure water, wherein the second texturizing additive includes a surfactant, a defoaming agent, sodium polystyrene sulfonate, sodium citrate, sodium dodecyl sulfonate and sodium benzoate.

[0026] The present invention also provides a PERC battery, which is prepared by the above method.

[0027] Compared with the prior art, the embodiments of the present invention have the following advantages:

[0028] In an embodiment of the present invention, a method for preparing a PERC cell is provided. After a single-crystalline silicon wafer is subjected to double-sided texturing and phosphorus diffusion treatment in sequence, the phosphosilicate glass on the back of the silicon wafer is first removed, and then the back of the silicon wafer is subjected to alkali polishing. Then, the back of the silicon wafer is subjected to single-sided texturing, and then the phosphosilicate glass on the front of the silicon wafer is removed. Finally, a passivation film layer, an anti-reflection layer and an electrode are formed on the surface of the silicon wafer to prepare a PERC cell. Wherein, while using the front borosilicate glass as a mask for the front texturing, a micro-texturing process is added to the back after the alkali polishing treatment, so that a small texturing structure is prepared on the back of the solar cell. The advantages of the small texturing structure can enhance the absorption of long-wave light, increase the current of the cell, enhance the efficiency of the back of the cell, increase the cell efficiency and the bifaciality, and at the same time provide an attachment point for the nucleation of the silver paste or aluminum paste on the back during the printing process, increase the contact ability between the silver paste and the silicon wafer, and enhance the filling of the cell.

[0029] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a flow chart of a method for preparing a PERC battery provided in an embodiment of the present invention;

[0031] Figure 2 3D microscope test image of the back side of the silicon wafer before oxidation annealing in Example 1;

[0032] Figure 3 The back side of the silicon wafer before oxidation annealing in Comparative Example 1 was subjected to a 3D microscope test image. DETAILED DESCRIPTION

[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0034] The applicant of the present invention has found that the manufacturing process of conventional PERC cells includes at least seven steps, including texturing, diffusion, etching, annealing, back film, front film and printing. Among them, the etching process requires polishing the back of the cell to make the back velvet structure relatively flat and the reflectivity of light is 40-50%, resulting in poor photoelectric conversion efficiency of the cell.

[0035] In order to solve the above problems, the present invention provides a method for preparing a PERC battery, wherein: Figure 1 As shown, it includes steps 101 to 105:

[0036] Step 101, after the single crystal silicon wafer is subjected to double-sided texturing and phosphorus diffusion treatment in sequence, the phosphorus silicon glass on the back side of the silicon wafer is removed;

[0037] Step 102, after removing the phosphosilicate glass on the back side, performing alkali polishing on the back side of the silicon wafer;

[0038] Step 103, after the alkali polishing treatment, performing a single-side texturing treatment on the back side of the silicon wafer;

[0039] Step 104, after single-sided texturing, removing the phosphosilicate glass on the front side of the silicon wafer;

[0040] Step 105: After removing the phosphosilicate glass on the front side, a passivation film layer, an anti-reflection layer and an electrode are formed on the surface of the silicon wafer to obtain a PERC cell.

[0041] In an embodiment of the present invention, after a single crystal silicon wafer is subjected to double-sided texturing and phosphorus diffusion treatment in sequence, the phosphosilicate glass on the back of the silicon wafer is first removed, and then the back of the silicon wafer is subjected to alkali polishing, and then the back of the silicon wafer is subjected to single-sided texturing, wherein the front borosilicate glass is used as a mask to protect the front texturing surface, and a micro-texturing process is added to the back after the alkali polishing treatment, so that a small texturing structure is prepared on the back of the solar cell. The advantages of the small texturing structure can enhance the absorption of long-wave light, increase the current of the cell, and enhance the efficiency of the back of the cell, thereby increasing the cell efficiency and double-sidedness, and at the same time provide an attachment point for the nucleation of the silver paste or aluminum paste on the back during the printing process, increase the contact ability between the silver paste and the silicon wafer, and enhance the filling of the cell; after the single-sided texturing treatment on the back, the phosphosilicate glass on the front of the silicon wafer is removed, and finally a passivation film layer, an anti-reflection layer and an electrode are formed on the surface of the silicon wafer, and a PERC cell can be obtained.

[0042] Optionally, in one embodiment, in the above step 101, the double-sided texturing process includes:

[0043] The back side of the silicon wafer is wet-textured using a second texturizing liquid, wherein the second texturizing liquid includes, by volume, 2 to 6 parts of 45% concentrated KOH, 1 to 2 parts of a second texturizing additive and 80 to 100 parts of pure water, wherein the second texturizing additive includes a surfactant, a defoaming agent, sodium polystyrene sulfonate, sodium citrate, sodium dodecyl sulfonate and sodium benzoate.

[0044] In this embodiment, KOH is used in combination with a second texturing additive to perform a trench texturing treatment on a silicon wafer, wherein the mass percentage concentration of KOH is 2.8-6.75%, the volume percentage of concentrated KOH is 2-6%, the volume percentage of the texturing additive is 1-2%, the treatment time is 200-300s, and the treatment temperature is 75-85°C.

[0045] In this embodiment, the silicon wafer is texturized with a KOH solution provided with a second texturizing additive, wherein the mass percentage concentration of KOH can be one of 2.8%, 3%, 4%, 5%, 6%, 6.75% or any two of the range values, the volume percentage concentration of the second texturizing additive can be one of 1%, 1.5%, 2% or any two of the range values, the processing time can be 220s, and the processing temperature can be 78°C.

[0046] Specifically, the silicon wafer may be a P-type single crystal silicon wafer. After double-sided texturing treatment, the reflectivity of the front side of the silicon wafer is less than 10%.

[0047] Optionally, in one embodiment, the second texturing additive may include, by mass percentage, 2-4% surfactant, 1-2% deaerator, 4-6% sodium polystyrene sulfonate, 0.5-2% sodium citrate, 1-2% sodium dodecyl sulfonate, 0.5-2% sodium benzoate, and the rest is water. Among them, the surfactant may be at least one of fatty alcohol polyoxyethylene ether sodium sulfate and triglyceride, and the deaerator may be propylene glycol ether.

[0048] Optionally, in a specific embodiment, the second texturing additive may include, by mass percentage, 3% surfactant, 2% defoaming agent, 5% sodium polystyrene sulfonate, 1% sodium citrate, 1.5% sodium dodecyl sulfonate, 1% sodium benzoate, and the rest is water.

[0049] Optionally, in one embodiment, in the above step 101, the phosphorus diffusion process includes:

[0050] Phosphorus diffusion deposition is performed on the silicon wafer for 10 to 15 minutes at a temperature of 770 to 790°C, a pressure of 70 to 120 mbar, a nitrogen flow rate of 500 to 800 sccm / min carrying phosphorus oxychloride, and an oxygen flow rate of 400 to 600 sccm / min. The temperature is then raised to 850 to 900°C, the pressure is 80 to 120 mbar, and the nitrogen flow rate is 2000 to 4000 sccm / min for 10 to 20 minutes.

[0051] In this step, after double-sided texturing, the silicon wafer is subjected to phosphorus oxychloride diffusion deposition, the deposition temperature is 770-790°C, the pressure is 70-120mbar, the nitrogen flow rate carrying phosphorus oxychloride is 500-800sccm / min, the oxygen flow rate is 400-600sccm / min, the deposition time is 10-15min, and then the temperature is raised to 850-900°C for advancement, the advancement time is 10-20min, and the pressure is 80-120mbar, that is, the surface phosphorus doping concentration of 3E20-5E20 / cm 3 The phosphorus diffusion layer.

[0052] Among them, because phosphorus oxychloride is in liquid form and cannot be directly introduced into the furnace tube, it needs to be carried into the furnace tube through moistened nitrogen at 20°C and quantified by the amount of nitrogen carried by the source.

[0053] The deposition temperature may be 770° C., 780° C., 790° C. or any two of the range values, the deposition pressure may be 70 mbar, 80 mbar, 90 mbar, 100 mbar, 110 mbar, 120 mbar or any two of the range values, the nitrogen flow rate carrying phosphorus oxychloride may be 500 sccm / min, 600 sccm / min, 700 sccm / min, 800 sccm / min or any two of the range values, the oxygen flow rate may be 400 sccm / min, 500 The pushing temperature can be one of 845°C, 860°C, 880°C or any two of the range values, the pushing time can be one of 10min, 15min, 20min or any two of the range values, and the pushing pressure can be one of 80mbar, 90mbar, 100mbar, 110mbar, 120mbar or any two of the range values.

[0054] Optionally, in one embodiment, after the phosphorus diffusion treatment, the thickness of the phosphorus-silicate glass on the front side of the silicon wafer is greater than or equal to 30 nm, which can effectively cover the front velvet surface and prevent it from being removed by alkali polishing. Optionally, the thickness of the phosphorus-silicate glass on the front side is less than or equal to 50 nm, which is convenient for subsequent removal by chain pickling. For example, after the phosphorus diffusion treatment, the thickness of the phosphorus-silicate glass on the front side of the silicon wafer can be a range of one or any two of 30 nm, 40 nm or 50 nm.

[0055] Optionally, in one embodiment, in the above step 101, removing the phosphosilicate glass on the back side of the silicon wafer includes:

[0056] The back side of the silicon wafer is chain-picked with hydrofluoric acid having a mass percentage of 4.9-9.8%.

[0057] In this embodiment, the back side of the silicon wafer subjected to phosphorus diffusion treatment is chain pickled using hydrofluoric acid with a mass percentage of 4.9 to 9.8% for 100 to 150 seconds to remove the phosphorus silicon glass layer on the back side.

[0058] The mass percentage of hydrofluoric acid may be in the range of one or any two of 4.9%, 6%, 7.35%, 8%, and 9.8%.

[0059] Optionally, in one embodiment, in the above step 102, the alkali polishing treatment includes:

[0060] The silicon wafer is wet-alkaline polished with an alkaline polishing liquid, wherein the alkaline polishing liquid includes, by volume, 12 to 18 parts of 45% concentrated KOH, 1 to 2 parts of an alkaline polishing additive and 400 to 500 parts of pure water, and the alkaline polishing additive includes alcohol ether phosphate, polyphosphate, polycarboxylic acid sulfonate, ethylene glycol ditetraacetic acid, sodium hypophosphite and sodium hydroxide.

[0061] In this embodiment, the silicon wafer is alkali-polished by a KOH solution containing an alkali-polishing additive, wherein the alkali-polishing treatment time is 160 to 260 seconds and the treatment temperature can be 70 to 80° C.; for example, the alkali-polishing treatment time can be 180 seconds and the treatment temperature can be 76° C.

[0062] Optionally, in a specific embodiment, the alkali polishing additive may include, by mass percentage, 1-3% of alcohol ether phosphate, 2-3% of polyphosphate, 1-2% of polycarboxylic acid sulfonate, 2-3% of ethylene glycol ditetraacetic acid, 0.1-0.5% of sodium hypophosphite, 0.5-2% of sodium hydroxide, and the rest is water.

[0063] Optionally, in a specific embodiment, the alkali polishing additive may include, by mass percentage, 2% of alcohol ether phosphate, 1.5% of polyphosphate, 1.3% of polycarboxylic acid sulfonate, 2.5% of ethylene glycol ditetraacetic acid, 0.1% of sodium hypophosphite, 1% of sodium hydroxide, and the rest is water; wherein the polyphosphate is pentasodium tripolyphosphate, and the polycarboxylic acid sulfonate is sodium methyl methacrylate sulfonate.

[0064] Optionally, in one implementation, the above step 103 includes:

[0065] The back side of the silicon wafer is wet-textured using a first texturizing liquid, wherein the first texturizing liquid includes, by volume, 12 to 18 parts of 45% concentrated KOH, 1 to 2 parts of a first texturizing additive and 400 to 500 parts of pure water, wherein the first texturizing additive includes isotridecanol ether, acrylamide, quaternary ammonium salt, disodium tetraacetate, alkyl glycoside and sodium benzoate.

[0066] In this embodiment, KOH combined with the first texturing additive is used to perform a groove texturing treatment on the back side of the silicon wafer after alkali polishing. The treatment time is 80 to 150 seconds and the treatment temperature is 70 to 80°C. A slight velvet surface can be prepared on the back side of the silicon wafer, and the reflectivity of the back side of the silicon wafer is controlled between 25 and 40%.

[0067] Specifically, the texturing treatment time may be 120 seconds, and the treatment temperature may be 75°C.

[0068] Optionally, in one embodiment, calculated by mass percentage, in the above-mentioned first texturing additive, the mass percentage of isotridecanol ether is 2-3%, the mass percentage of acrylamide is 0.5-2%, the mass percentage of quaternary ammonium salt is 1-3%, the mass percentage of disodium tetraacetate is 1-3%, the mass percentage of alkyl glycoside is 3-4%, the mass percentage of sodium benzoate is 0.3-0.5%, and the balance is water.

[0069] Optionally, in a specific embodiment, in the above-mentioned first texturing additive, calculated by mass percentage, the mass percentage of isotridecanol ether is 2.5%, the mass percentage of acrylamide is 1%, the mass percentage of quaternary ammonium salt is 2%, the mass percentage of disodium tetraacetate is 2%, the mass percentage of alkyl glycoside is 3.5%, the mass percentage of sodium benzoate is 0.4%, and the remainder is water; wherein, the quaternary ammonium salt is dodecyltrimethylammonium chloride.

[0070] Optionally, in one implementation, the above step 104 includes:

[0071] The back side of the silicon wafer is chain-picked with hydrofluoric acid having a mass percentage of 4.9 to 9.8%.

[0072] In this embodiment, the back side of the silicon wafer treated with phosphorus diffusion is chain-picked using hydrofluoric acid with a mass percentage of 4.9-9.8% to remove the phosphorus-silicate glass layer on the back side.

[0073] The mass percentage of hydrofluoric acid may be in the range of one or any two of 4.9%, 6%, 6.86%, 8%, and 9.8%.

[0074] Optionally, in one embodiment, the passivation film layer includes aluminum oxide, and has a thickness of 6 to 10 nm, for example, a range of one or any two of 6 nm, 8 nm, and 10 nm.

[0075] Optionally, in one embodiment, the anti-reflection layer includes silicon nitride, and has a thickness of 70 to 84 nm, for example, a range of one or any two of 70 nm, 75 nm, and 84 nm.

[0076] Optionally, in one implementation, the above step 105 further includes step 1051:

[0077] After forming the passivation film layer, plasma enhanced chemical vapor deposition is performed for 700 to 1000 seconds under the conditions of a silane flow rate of 1200 to 1800 sccm / min, an ammonia flow rate of 8500 to 1200 sccm / min, a pressure of 1500 to 1800 mtorr, and a radio frequency power of 8000 to 11000 w to form the anti-reflection layer.

[0078] In this step, the silane and ammonia introduced into the furnace tube are ionized by the oscillating ionization effect of the radio frequency device to form a plasma, and then silicon nitride is grown by reaction on the surface of silicon dioxide to form an anti-reflection layer.

[0079] Wherein, in the above step 1051, the flow rate of silane can be one of 1200sccm / min, 1550sccm / min, 1800sccm / min or any two of the range values, the flow rate of ammonia can be one of 8500sccm / min, 9600sccm / min, 12000sccm / min or any two of the range values, the pressure can be one of 1500mtorr, 1600mtorr, 2000mtorr or any two of the range values, the RF power can be one of 8000w, 9000w, 11000w or any two of the range values, and the deposition time can be one of 700s, 850s, 1000s or any two of the range values.

[0080] Optionally, in a specific embodiment, the anti-reflection layer includes a front anti-reflection layer and a back anti-reflection layer; wherein the thickness of the front anti-reflection layer is 70 to 85 nm and the refractive index is 2.0 to 2.05, for example, it can be one of 70 nm, 75 nm, 70 nm, 85 nm or any two of the range values; the thickness of the back anti-reflection layer is 75 to 95 nm and the refractive index is 2.05 to 2.15, for example, it can be one of 75 nm, 80 nm, 85 nm, 90 nm, 95 nm or any two of the range values.

[0081] Optionally, in one embodiment, in the above step 105, after the anti-reflection layer is formed on both the front and back sides of the product, the front and back metal electrodes are prepared by screen printing, and then sintered to obtain a PERC cell. The front and back mother grids use silver paste, the front sub-grids use silver aluminum paste, and the back sub-grids use silver paste. The sintering temperature is 750-800°C and the sintering time is 30-60S.

[0082] Optionally, in one embodiment, the preparation method provided in the embodiment of the present invention further includes step 1050 before step 104 and before step 105:

[0083] The silicon wafer is subjected to oxidation annealing treatment for 20 to 40 minutes at a temperature of 700 to 760° C., a pressure of 400 to 700 mbar, and an oxygen flow rate of 3000 to 5000 sccm / min.

[0084] In this embodiment, a 3-7 nm silicon dioxide layer can be grown on the surface of the silicon wafer through oxidation annealing treatment to passivate the dangling bonds on the surface of the silicon wafer.

[0085] The present invention also provides a PERC battery, which is prepared by the above method.

[0086] The present invention is described in detail below by way of examples.

[0087] Example 1

[0088] (1) Select a 182mm×182mm P-type silicon wafer, and use KOH combined with a second texturing additive to perform a groove-type double-sided texturing treatment on the silicon wafer, wherein, by volume, the texturing solution includes 4.5 parts of 45% concentrated KOH, 1.5 parts of the second texturing additive, and 94 parts of pure water; wherein the second texturing additive includes 3% by mass of sodium polyoxyethylene fatty alcohol ether sulfate, 2% by mass of propylene glycol ether, 5% by mass of sodium polystyrene sulfonate, 1% by mass of sodium citrate, 1.5% by mass of sodium dodecyl sulfonate, 1% by mass of sodium benzoate, and the rest is water;

[0089] (2) Phosphorus diffusion deposition was performed on the silicon wafer for 12 min at a temperature of 780°C, a pressure of 80 mbar, a nitrogen flow rate of 700 sccm / min carrying phosphorus oxychloride, and an oxygen flow rate of 500 sccm / min, and then the temperature was raised to 860°C and advanced for 15 min at a pressure of 100 mbar and a nitrogen flow rate of 2000 sccm / min;

[0090] (3) Using 7.35% by mass hydrofluoric acid to chain pickle the back of the silicon wafer;

[0091] (4) Wet alkali polishing of silicon wafers using KOH combined with alkali polishing additives, wherein, by volume, the alkali polishing solution includes 15 parts of 45% concentrated KOH, 1.5 parts of alkali polishing additives and 450 parts of pure water, the alkali polishing additives include 2% alcohol ether phosphate, 1.5% polyphosphate, 1.3% polycarboxylic acid sulfonate, 2.5% ethylene glycol ditetraacetic acid, 0.1% sodium hypophosphite, 1% sodium hydroxide, and the rest is water; wherein the polyphosphate is pentasodium tripolyphosphate, the polycarboxylic acid sulfonate is sodium methyl methacrylate sulfonate, the treatment time is 180 seconds, and the treatment temperature is 76°C;

[0092] (5) After the alkaline polishing treatment, the back side of the silicon wafer is subjected to a groove-type single-sided texturing treatment using KOH combined with a first texturing additive, wherein, by volume, the texturing solution includes 15 parts by mass of 45% concentrated KOH, 2.5 parts by mass of the first texturing additive and 450 parts by mass of pure water, the texturing treatment time is 120 seconds, and the treatment temperature is 75°C, wherein the first texturing additive includes 3% by mass of a surfactant, 2% by mass of a degassing agent, 5% by mass of sodium polystyrene sulfonate, 1% by mass of sodium citrate, 1.5% by mass of sodium dodecyl sulfonate, 1% by mass of sodium benzoate, and the remainder is water;

[0093] (6) Use 6.89% by mass hydrofluoric acid to pickle the phosphosilicate glass on the front side of the silicon wafer for 140 seconds;

[0094] (7) performing oxidation annealing treatment on the silicon wafer, wherein the annealing temperature is 720° C. and the time is 30 min;

[0095] (8) performing a back-side coating process on the silicon wafer, coating aluminum oxide and silicon nitride respectively, thereby forming a back-side passivation layer and a back-side anti-reflection layer, wherein the thickness of the aluminum oxide is 10 nm and the thickness of the silicon nitride is 75 nm;

[0096] (9) Under the conditions of a silane flow rate of 1550 sccm / min, an ammonia flow rate of 9600 sccm / min, a pressure of 1600 mtorr, and a radio frequency power of 9000 W, plasma enhanced chemical vapor deposition was performed on the front surface for 850 s to form a silicon nitride layer with a thickness of 77 nm as a front anti-reflection layer;

[0097] (10) The front and back metal electrodes were prepared by screen printing, and silver paste was printed on the front and back grid lines. Then, the cells were sintered at 790°C for 35 seconds to obtain a PERC cell.

[0098] The above-mentioned Example 1 was repeated to obtain 2500 PERC cells. The electrical performance of each PERC cell was tested and the average value was calculated. The results are shown in Table 1.

[0099] Comparative Example 1

[0100] (1) Select a 182mm×182mm P-type silicon wafer, and use KOH combined with a second texturing additive to perform a groove-type double-sided texturing treatment on the silicon wafer, wherein, by volume, the texturing solution includes 4.5 parts of 45% concentrated KOH, 1.5 parts of the second texturing additive, and 94 parts of pure water; wherein the second texturing additive includes 3% by mass of sodium polyoxyethylene fatty alcohol ether sulfate, 2% by mass of propylene glycol ether, 5% by mass of sodium polystyrene sulfonate, 1% by mass of sodium citrate, 1.5% by mass of sodium dodecyl sulfonate, 1% by mass of sodium benzoate, and the rest is water;

[0101] (2) Phosphorus diffusion deposition was performed on the silicon wafer for 12 min at a temperature of 780°C, a pressure of 80 mbar, a nitrogen flow rate of 700 sccm / min carrying phosphorus oxychloride, and an oxygen flow rate of 500 sccm / min, and then the temperature was raised to 860°C and advanced for 15 min at a pressure of 100 mbar and a nitrogen flow rate of 2000 sccm / min;

[0102] (3) Using 7.35% by mass hydrofluoric acid to chain pickle the back of the silicon wafer;

[0103] (4) Wet alkali polishing of silicon wafers using KOH combined with alkali polishing additives, wherein, by volume, the alkali polishing solution includes 15 parts of 45% concentrated KOH, 1.5 parts of alkali polishing additives and 450 parts of pure water, the alkali polishing additives include 2% alcohol ether phosphate, 1.5% polyphosphate, 1.3% polycarboxylic acid sulfonate, 2.5% ethylene glycol ditetraacetic acid, 0.1% sodium hypophosphite, 1% sodium hydroxide, and the rest is water; wherein the polyphosphate is pentasodium tripolyphosphate, the polycarboxylic acid sulfonate is sodium methyl methacrylate sulfonate, the treatment time is 180 seconds, and the treatment temperature is 76°C;

[0104] (5) After the alkaline polishing treatment, the phosphosilicate glass on the front side of the silicon wafer is pickled with hydrofluoric acid having a mass percentage of 6.89%, and the treatment time is 140 seconds;

[0105] (6) performing oxidation annealing treatment on the silicon wafer, wherein the annealing temperature is 720° C. and the time is 30 min;

[0106] (7) performing a back-side coating process on the silicon wafer, coating aluminum oxide and silicon nitride respectively, thereby forming a back-side passivation layer and a back-side anti-reflection layer, wherein the thickness of the aluminum oxide is 10 nm and the thickness of the silicon nitride is 75 nm;

[0107] (8) Under the conditions of silane flow rate of 1550 sccm / min, ammonia flow rate of 9600 sccm / min, pressure of 1600 mtorr, and RF power of 9000 W, plasma enhanced chemical vapor deposition was performed on the front surface for 850 s to form a silicon nitride layer with a thickness of 77 nm as a front anti-reflection layer;

[0108] (9) The front and back metal electrodes were prepared by screen printing, and silver paste was printed on the front and back grid lines. Then, the cells were sintered at 790°C for 35 seconds to obtain a PERC cell.

[0109] The above comparative example 1 was repeated to obtain 2,300 PERC cells. The electrical performance of each PERC cell was tested and the average value was calculated. The results are shown in Table 1.

[0110] Table 1

[0111]

[0112] Experiments show that compared with conventional processes, the embodiment of the present invention performs single-sided texturing on the back of the silicon wafer after alkali polishing, and the opening voltage of the PERC battery obtained is basically the same, but the current is increased by 25mA, and the fill factor is increased by 0.24%. This shows that the texturing on the back increases the absorption of long-wave light, improves the current of the battery cell, provides an attachment point for the silver paste particles on the back during the sintering process, increases the ohmic contact, and improves the photoelectric conversion efficiency of the battery cell.

[0113] The back side of the silicon wafer before oxidation annealing in Example 1 and Comparative Example 1 was tested by 3D microscope, and the results are as follows: Figures 2-3 shown.

[0114] contrast Figure 2 and Figure 3 It can be seen that the single-sided texturing treatment on the back of the silicon wafer after alkali polishing causes an increase in black spots near the base of the test tower and an increase in the number of small pyramid texturing surfaces on the surface.

[0115] In summary, in the present embodiment, the preparation method of the PERC cell provided is, after the monocrystalline silicon wafer is subjected to double-sided texturing and phosphorus diffusion treatment in sequence, the phosphosilicate glass on the back of the silicon wafer is first removed, and then the back of the silicon wafer is subjected to alkali polishing, and then the back of the silicon wafer is subjected to single-sided texturing, and then the phosphosilicate glass on the front of the silicon wafer is removed, and finally a passivation film layer, an anti-reflection layer and an electrode are formed on the surface of the silicon wafer to obtain a PERC cell; wherein, when the front borosilicate glass is used as a mask for the front texturing, a micro-texturing process is added to the back after the alkali polishing treatment, so that a small texturing structure is prepared on the back of the solar cell. The advantages of the small texturing structure can enhance the absorption of long-wave light, increase the current of the cell, enhance the efficiency of the back of the cell, increase the cell efficiency and the double-sided rate, and at the same time provide an attachment point for the nucleation of the silver paste or aluminum paste on the back during the printing process, increase the contact ability between the silver paste and the silicon wafer, and enhance the filling of the cell.

[0116] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.

[0117] The PERC battery and the preparation method thereof provided by the present invention are introduced in detail above. The principle and implementation mode of the present invention are explained by using specific examples herein. The description of the above embodiments is only used to help understand the method and the core idea of ​​the present invention. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation mode and the scope of application. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for preparing a PERC battery, characterized in that: include: After the single crystal silicon wafer is subjected to double-sided texturing and phosphorus diffusion treatment in sequence, the phosphorus silicon glass on the back side of the silicon wafer is removed; After removing the phosphorus silicon glass on the back side, the back side of the silicon wafer is subjected to alkali polishing; After the alkali polishing treatment, the back side of the silicon wafer is subjected to a single-side texturing treatment; After single-sided texturing, removing the phosphosilicate glass on the front side of the silicon wafer; After removing the phosphosilicate glass on the front side, a passivation film layer, an anti-reflection layer and an electrode are formed on the surface of the silicon wafer to produce a PERC cell.

2. The method for preparing a PERC cell according to claim 1, characterized in that: The back side of the silicon wafer is subjected to a single-side texturing process, comprising: The back side of the silicon wafer is wet-textured using a first texturizing liquid, wherein the first texturizing liquid includes, by volume, 12 to 18 parts of 45% concentrated KOH, 1 to 2 parts of a first texturizing additive and 400 to 500 parts of pure water, wherein the first texturizing additive includes isotridecanol ether, acrylamide, quaternary ammonium salt, disodium tetraacetate, alkyl glycoside and sodium benzoate.

3. The method for preparing a PERC cell according to claim 2, characterized in that: In the first texturing additive, the mass percentage of isotridecanol ether is 2-3%, the mass percentage of acrylamide is 0.5-2%, the mass percentage of quaternary ammonium salt is 1-3%, the mass percentage of disodium tetraacetate is 1-3%, the mass percentage of alkyl glycoside is 3-4%, the mass percentage of sodium benzoate is 0.3-0.5%, and the balance is water.

4. The method for preparing a PERC cell according to claim 2, characterized in that: The single-sided texturing treatment time is 80 to 150 seconds, and the treatment temperature is 70 to 80°C.

5. The method for preparing a PERC cell according to claim 2, characterized in that: After single-sided texturing, the reflectivity of the back side of the silicon wafer is between 25% and 40%.

6. The method for preparing a PERC cell according to claim 1, characterized in that: Phosphorus diffusion treatment includes: Phosphorus diffusion deposition is performed on the silicon wafer for 10 to 15 minutes at a temperature of 770 to 790°C, a pressure of 70 to 120 mbar, a nitrogen flow rate of 500 to 800 sccm / min carrying phosphorus oxychloride, and an oxygen flow rate of 400 to 600 sccm / min. The temperature is then raised to 850 to 900°C, the pressure is 80 to 120 mbar, and the nitrogen flow rate is 2000 to 4000 sccm / min for 10 to 20 minutes.

7. The method for preparing a PERC cell according to claim 6, characterized in that: After the phosphorus diffusion treatment, the thickness of the phosphorus-silicate glass on the front side of the silicon wafer is greater than or equal to 30 nm.

8. The method for preparing a PERC cell according to claim 1, characterized in that: Removing the phosphosilicate glass on the back side of the silicon wafer, comprising: The back side of the silicon wafer is chain pickled using 4.9-9.8% hydrofluoric acid by mass; Removing the phosphosilicate glass on the front side of the silicon wafer, comprising: The front side of the silicon wafer is chain pickled using hydrofluoric acid with a mass percentage of 4.9-9.8%.

9. The method for preparing a PERC cell according to claim 1, characterized in that: The double-sided velveting comprises: The back side of the silicon wafer is wet-textured using a second texturizing liquid, wherein the second texturizing liquid includes, by volume, 2 to 6 parts of 45% concentrated KOH, 1 to 2 parts of a second texturizing additive and 80 to 100 parts of pure water, wherein the second texturizing additive includes a surfactant, a defoaming agent, sodium polystyrene sulfonate, sodium citrate, sodium dodecyl sulfonate and sodium benzoate.

10. A PERC battery, characterized in that: The method is prepared by any one of claims 1 to 9.